This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
S S S = ⌊ x + 1 0 0 1 ⌋ + ⌊ x + 1 0 0 2 ⌋ + … + ⌊ x + 1 0 0 2 2 3 ⌋ = 5 2 1 = 3 ( ⌊ x + 1 0 0 1 ⌋ + ⌊ x + 1 0 0 2 ⌋ + … + ⌊ x + 1 0 0 2 3 ⌋ ) + 2 ( ⌊ x + 1 0 0 2 4 ⌋ + ⌊ x + 1 0 0 2 5 ⌋ + … + ⌊ x + 1 0 0 1 0 0 ⌋ ) = 5 2 1 − 1 0 0 − 2 3 × 2 = 3 7 5 ⇒ x = ⌊ x ⌋ + { x } = 2 2 3 ⌊ x ⌋ + 3 ∑ 2 3 n = 1 ⌊ { x } + 1 0 0 n ⌋ + 2 m = 2 4 ∑ 1 0 0 ⌊ { x } + 1 0 0 m ⌋ = 3 7 5 = 3 7 5 , ⌊ x ⌋ = ⌊ 2 2 3 3 7 5 ⌋ = 1 ⇒ 3 n = 1 ∑ 2 3 ⌊ { x } + 1 0 0 n ⌋ + 2 m = 2 4 ∑ 1 0 0 ⌊ { x } + 1 0 0 m ⌋ = 3 7 5 − 2 2 3 = 1 5 2
Now we can obviously see that any term of ( ⌊ x + 1 0 0 n ⌋ ) n = 1 2 3 would be smaller than any term of ( ⌊ x + 1 0 0 n ⌋ ) n = 2 4 1 0 0 , so 1 5 2 would coming from 2 m = 2 4 ∑ 1 0 0 ⌊ { x } + 1 0 0 m ⌋ and note that the terms can't be greater than 1 . If all the terms equal 1 , then 2 m = 2 4 ∑ 1 0 0 ⌊ { x } + 1 0 0 m ⌋ = 1 5 4 , so to decrease 2 and get 1 5 2 as our result, all the terms of ( ⌊ { x } + 1 0 0 m ⌋ ) m = 2 5 1 0 0 must be equal to 1 .
∴ { x } + 1 0 0 2 5 { x } x ⇒ ⌊ 1 0 0 x ⌋ ≥ 1 ≥ 0 . 7 5 = ⌊ x ⌋ + { x } = 1 + 0 . 7 5 = 1 . 7 5 = 1 7 5